Social and emotional learning in education and care policy in Croatia - Maja Ljubetic; Toni Maglica (International Journal of Evaluation and Research in Education (IJERE), 2020)
Worldwide practises and then scientific research is showing that social-emotional learning represents a highly promising approach for positive development and adjustment, improvement of academic success in children and even prevention of behavioural problems. But despite these findings, there is no systematic approach in the implementation of the social-emotional learning in Croatia, and the practice of it is not yet structured and comprehensive and occurs rather occasionally and spontaneously. This paper is trying to ascertain is there a formal and legal platform for implementing social-emotional learning in the crucial documents that regulate educational and care practises in Croatia. The analysis of the documents was conducted according to the criterium of key social-emotional competencies and the associated social-emotional skills.